Reproductive planning in indigenous area and the search for differentiated attention: the dilemmas between inequality and difference - Ávila, Bruna Teixeira; Alves, Sandra Valongueiro (Saúde e Sociedade, 2022)
Differentiated care is a fundamental principle for non-colonizing care for indigenous populations. One of the challenges in this field is reproductive planning, as it involves tensions between collective and individual wills, in addition to the guardianship and the autonomy, especially with the more continuous insertion of professionals with the Mais Médicos Program, as occurred in the Yanomami Territory. This study aims to discuss the aspects involved in differentiated attention to reproductive planning, by comparing the work of health professionals in indigenous and non-indigenous areas. To this end, an ethnographic case study based on participant observation of the teams’ exercise accessed by the Supervision of the Mais Médicos Program and interviews with six professionals, selected for their diversity of their profile. From the content analysis, three categories were identified: difference and inequality, similarities; and challenges. These divisions bring the notion of physiological comparison, which generates a biomedical approach, going through the confusion between difference and inequality, the aspect responsible for favoring colonization and the denial of rights – and even the understandings of professionals about the culture – which cross the intercultural dialogue.